2015
DOI: 10.1002/jat.3257
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional and morphological effects of tamoxifen on the early development of zebrafish (Danio rerio)

Abstract: Tamoxifen is a widely used anticancer drug with both an estrogen agonist and antagonist effect. This study focused on its endocrine disrupting effect, and overall environmental significance. Zebrafish embryos were exposed to different concentrations (0.5, 5, 50 and 500 µg l(-1) ) of tamoxifen for 96 h. The results showed a complex effect of tamoxifen on zebrafish embryo development. For the 500 µg l(-1) exposure group, the heart rate was decreased by 20% and mild defects in caudal fin and skin were observed. E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(8 citation statements)
references
References 44 publications
0
8
0
Order By: Relevance
“…However, it has been reported that estrogenic ligands can alter the basal heart rate in zebrafish embryos. Exposure to estradiol and ICI 182,780 resulted in increased heart rate in zebrafish, an effect that was attributed to modulation of the G proteincoupled estrogen receptor (GPER) pathway (Romano et al, 2016), while treatment with the anti-estrogen tamoxifen caused a decrease in the heart rate of zebrafish embryos (Xia et al, 2016). BPA treatment has been shown to impair the cardiac contractile performance of rodent hearts, an effect associated with altered intracellular calcium handling (Posnack et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…However, it has been reported that estrogenic ligands can alter the basal heart rate in zebrafish embryos. Exposure to estradiol and ICI 182,780 resulted in increased heart rate in zebrafish, an effect that was attributed to modulation of the G proteincoupled estrogen receptor (GPER) pathway (Romano et al, 2016), while treatment with the anti-estrogen tamoxifen caused a decrease in the heart rate of zebrafish embryos (Xia et al, 2016). BPA treatment has been shown to impair the cardiac contractile performance of rodent hearts, an effect associated with altered intracellular calcium handling (Posnack et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Similar to human CYP3A, enhanced CYP3A65 transcription in the foregut of the zebrafish larvae in response to dexamethasone and the antibiotic rifampicin confirmed that zebrafish CYP3A65 is an ortholog of the human CYP3A gene (Chang et al, ; Tseng et al, ). CYP3A65 expression in zebrafish has been used as a hepatic biomarker (Al‐Habsi et al, ; Cunha et al, ; Verstraelen et al, ; Xia et al, ) and the zebrafish embryo model was shown to detect hepatotoxicants with higher specificity than the HepG2 cells (Jones et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Tamoxifen may reverse the effects of estradiol and BPA. 36 It has also been reported that BPA metabolites can be converted into glutathione conjugates in order to be excreted in urine. Thus, the expression of the GSTP1 gene may be responsible for conjugation of BPA metabolites with glutathione, which could increase with BPA exposure.…”
Section: Discussionmentioning
confidence: 99%